Aspect ratio controlled synthesis of tellurium nanowires for photovoltaic applications. Issue 8 (18th August 2020) - Pokhrel, Dipendra; Bastola, Ebin; Phillips, Adam B.; Heben, Michael J.; Ellingson, Randy J.
Abstract : Here, we report an aspect ratio-controlled synthesis of tellurium (Te) nanowires (NWs) utilizing a hot injection colloidal method and demonstrate their use as a back buffer layer in cadmium telluride (CdTe) photovoltaics. Abstract : Here, we report an aspect ratio-controlled synthesis of tellurium (Te) nanowires (NWs) utilizing a hot-injection colloidal method. The synthetic method uses low cost materials – specifically, tellurium oxide (TeO2 ) as the tellurium source, environmentally benign ethylene glycol as a solvent, and ascorbic acid as a reducing agent. Analysis of scanning electron micrographs confirms that the NWs show narrow distributions for length, diameter, and therefore also aspect ratio. For example, we have prepared Te NWs exhibiting aspect ratios of 28.0 and 55.4. X-ray diffraction studies confirm a hexagonal crystal structure for the synthesized Te NWs. Based on Raman spectroscopy, Stokes lines were observed at 117.0 and 136.1 cm −1 for A1 and E2 modes of vibration. Fabrication of Te NW thin films demonstrated their suitability as a hole transport layer at the back contact of cadmium sulfide/cadmium telluride (CdS/CdTe) solar cells, yielding enhanced open-circuit voltage ( V oc = 0.846 V) and fill factor (FF = 77.8%), and an efficiency of 14.6%; the control device has an efficiency of 13.1% ( V oc = 0.825 mV, FF 74.0%).